Sociotechnical Requirements Analysis for Clinical Systems - Reddy, M., Ph.D.; Pratt, W., Ph.D.; Dourish, P., Ph.D.; Shabot, M. M., M.D. (Methods of Information in Medicine, 2003)
Objective: We explore sociotechnical requirements by examining the use of a computerized patient record system in an intensive care unit of a U.S. hospital and present two sociotechnical requirements, awareness and coordination, embedded in the users’ work.Method: The study is based on observation during seven months of the use of a computerized patient record system in a surgical intensive care unit. During that period semi-formal interviews, informal interviews were held.Results and Conclusions: A key step in the design of clinical systems is the development and analysis of requirements. However, traditional requirements analysis is based on a set of assumptions that break down in the highly collaborative, exception-filled clinical domain. Sociotechnical requirement analysis enabled the designers to gather a much richer description of the environment surrounding the computer system, highlighting awareness and coordination, embedded in the users’ work.
Keywords: Sociotechnical requirements analysis; clinical systems; computerized patient record system; collaborative work; intensive care unit